Hydrological hazard assessment: THE 2014–15 Malaysia floods - Ruiz Estrada, Mario Arturo; Koutronas, E.; Tahir, M.; Mansor, Norma (Elsevier, 2017)
This paper intends to establish conceptual foundations on the identification of standards and metrics for assessing the impact of hydrological hazards. The economic evaluation of flood damage cost model (EFDC-Model) attempts to estimate the impact of water occurrence, movement, and distribution on GNP growth. The model is based on seven basic indicators: (i) the national precipitation growth rate (∆Pi); (ii) the main factors which generate large precipitation (∆Li); (iii) the sinking magnitudes levels rate (ST); (iv) the national floods recurrence rate (FT); (v) the floods devastation rate (Dk); (vi) the economic desgrowth from floods devastation rate (-δf); and (vii) the floods damage surface. The model investigates the recent floods in the Malaysian states of Kelantan and Terengganu for the period 2014–2015.